On (Archival) Odyssey(s) - Harris, Verne (Archivaria, 2001)
This article closely resembles the author's keynote address to the Association of Canadian Archivists conference (2001), which had as its theme "The Archival Odyssey." At one level, it is an extended meditation on the resonances of meaning suggested by the conjunction of the three words in the conference theme. At another, it is a highly focused deconstruction of the theme. Harris lays bare the assumptions informing the theme as an exercise in meaning construction, and shows how these assumptions hold at bay, or exclude, significant dimensions of meaning construction. His concern is to invite these "spectres" in. If he has a conclusion, it is that "odyssey" is an unfortunate metaphor, or archetype, for archival endeavour. He proposes "adventure" -- destiny without destination -- as a potentially more enriching metaphor. RÉSUMÉ Cet article est basé sur la conférence d'ouverture présentée par l'auteur au congrès de 2001 de l'Association of Canadian Archivists dont le thème était "The Archival Odyssey". À un premier niveau, il s'agit d'une méditation étendue sur la résonance des différents sens suggérés par la conjonction des trois mots du thème de la conférence. À un autre niveau, c'est une déconstruction très focalisée de ce thème. L'auteur dévoile les postulats sous-tendant le thème comme exercice de construction de sens et montre comment ces postulats masquent ou excluent certaines dimensions significatives de cette construction. Son but est d'inviter ces «spectres» à apparaître au grand jour. S'il a une conclusion, c'est que le terme d'odyssée est une métaphore ou un archétype malheureux pour désigner l'entreprise archivistique. L'auteur propose plutôt le mot «aventure» -- un destin sans destination -- comme une métaphore potentiellement plus enrichissante.